The Effect of Halal Certificate, Food Quality and Price on Consumers’ Decision in Buying Aqeeqah Products - Pebriani, Diyan; Setiawan, Donny; Bayinah, Ai Nur (Jurnal Ekonomi dan Perbankan Syariah, 2023)
The purpose of this study is to analyze the effect of halal certificates, food quality, and price on purchasing decisions. The research method is quantitative. The data are collected using a questionnaire. The dependent variable is the purchase decision and the independent variable is the halal certificate, food quality, and price on the purchase decision of Aqeeqah products in Tangerang Regency. The data analysis method used is multiple linear regression. This study shows that halal certificates have no significant effect on purchasing decisions for Aqeeqah products in Tangerang District, while food quality and price have a significant effect on purchasing decisions for Aqeeqah products in Tangerang District. The results of the research from the simultaneous test of halal certificate variables, food quality, and price have a significant effect on purchasing decisions. This shows that people living in Tangerang Regency prioritize food quality and price rather than the legality of halal certificates when buying Aqeeqah products.